2019
DOI: 10.1002/fsn3.1056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leadership style and organizational climate on employees' food safety and hygiene behaviors in the institutional food service of schools

Abstract: This study took the employees working in the institutional food service of schools in northern Taiwan as subjects to explore the influences of leadership style and organizational climate on food safety and hygiene behaviors. In this study, 400 questionnaires were distributed and 324 valid questionnaires were collected, for a valid return rate of 81%. The results showed that leadership style and organizational climate positively correlate with employees' behaviors with respect to food safety and hygiene. Transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 42 publications
(60 reference statements)
2
24
0
2
Order By: Relevance
“…According to Hay Group's research, that one of the most significant strengths of an effective is his/her ability to create a positive work climate and effective leaders are shifting leadership styles to create a positive work climate in the areas they manage. This has been confirmed by several studies such as Ko and Kang (2019) that different leadership styles affect the organizational climate and the study of Dulay and Karadag (2015) on the effect of leadership styles on the organizational climate.…”
Section: Leadership and Organizational Climatesupporting
confidence: 60%
“…According to Hay Group's research, that one of the most significant strengths of an effective is his/her ability to create a positive work climate and effective leaders are shifting leadership styles to create a positive work climate in the areas they manage. This has been confirmed by several studies such as Ko and Kang (2019) that different leadership styles affect the organizational climate and the study of Dulay and Karadag (2015) on the effect of leadership styles on the organizational climate.…”
Section: Leadership and Organizational Climatesupporting
confidence: 60%
“…The first potential explanation involves the nature of these two types of organizational behavior. While organizational fairness and leadership attention are top-down relationships, organizational fairness focuses on institutionalism, whereas leadership attention is based on subjectivity (individual leaders) [ 12 , 15 , 17 , 39 , 40 ]. We argue that this relationship has similarities to the nature of football matches, with organizational fairness being similar to competition rules, and leadership attention being similar to the behavior of the referee.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cheung [ 31 ] found that organizational regulation of worksite noise helped promote employees’ protective behaviors for hearing loss. Ko and Kang [ 32 ] revealed that the organizational climate had a positive and significant influence on school dietitians’ food safety and hygiene behaviors. Schwatka et al [ 33 ] found that organizational safety and the health climate were positively correlated with the healthy behaviors of workers in small businesses.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%